2021
DOI: 10.3390/cells10030585
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Amyloid a Levels Are not Specific for Sarcoidosis but Associate with a Fibrotic Pulmonary Phenotype

Abstract: Elevated Serum Amyloid A (SAA) levels have been found in several inflammatory diseases, including sarcoidosis. SAA is suggested to be involved in sarcoidosis pathogenesis by involvement in granuloma formation and maintenance. We hypothesized that SAA serum levels would be higher in sarcoidosis compared to other non-infectious granulomatous and non-granulomatous diseases. SAA levels were measured in serum from sarcoidosis, Hypersensitivity pneumonitis (HP), and (eosinophilic) granulomatosis with polyangiitis ((… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(31 reference statements)
3
16
0
Order By: Relevance
“…In agreement with our study, other studies have reported elevated serum SAA levels in sarcoidosis patients, particularly with subacute onset requiring prolonged and multiple steroid treatments (Bargagli et al, 2011). In addition, fibrotic sarcoidosis patients showed higher SAA levels than sarcoidosis patients without fibrosis (Beijer et al, 2021). Further studies are needed to clarify the potential of SAA as a prognostic factor in NS.…”
Section: Blood-brain Barrier Disruption and Vascular Biomarkerssupporting
confidence: 90%
“…In agreement with our study, other studies have reported elevated serum SAA levels in sarcoidosis patients, particularly with subacute onset requiring prolonged and multiple steroid treatments (Bargagli et al, 2011). In addition, fibrotic sarcoidosis patients showed higher SAA levels than sarcoidosis patients without fibrosis (Beijer et al, 2021). Further studies are needed to clarify the potential of SAA as a prognostic factor in NS.…”
Section: Blood-brain Barrier Disruption and Vascular Biomarkerssupporting
confidence: 90%
“…The serum levels of SAA1, FGA, and SAP in the EGPA group were significantly elevated as compared to the healthy control and severe-asthma groups (Figures 4A-C), while the serum CETP was significantly lower in the EGPA group compared with the severe-asthma group (Figure 4D). It has been reported that serum SAA protein in EGPA patients is significantly higher than that in healthy subjects (40). The other three, FGA, SAP, and CETP, have not been reported as EGPA disease-related biomarkers so far, suggesting that we may have found new diagnostic biomarkers for EGPA.…”
Section: Identification Of Candidate Markersmentioning
confidence: 72%
“…Accumulating evidence indicates that elevated serum levels of SAA can be a clinical biomarker for inflammatory diseases (41). A recent study has shown that SAA levels in serum of EGPA patients were higher than in healthy controls by using the ELISA method, and it has suggested that SAA may reflect the process of fibrogenesis after the granulomatous process (40). Both DIA and PRM approaches applied in our study showed that serum SAA1 level in the EGPA group was not only significantly higher than that in the healthy control group, which was consistent with the previous study, but also significantly higher than the severe-asthma group.…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum levels in fibrotic versus nonfibrotic sarcoidosis [64]; amount of SAA staining in lung tissue correlated with fibrosis [63] Higher serum levels compared to healthy control [64,65] CCL-18 Unstimulated production of CCL-18 in BAL cells increased progressively comparing Scadding stages 1-4 [72] Serum levels linked to mortality [71] and unstimulated production of CCL-18 in BAL cells higher than control and fibrotic sarcoidosis [72] CD163 + macrophage presence in lung tissue…”
Section: Saa Levelsmentioning
confidence: 99%
“…CHEN et al [63] demonstrated that, in sarcoidosis lung samples with fibrosis (n=6), the extent of SAA staining positively correlated with the degree of collagen deposition. Following on from these data, BEIJER et al [64] measured SAA levels in serum from patients with sarcoidosis (n=215), hypersensitivity pneumonitis (n=30), (eosinophilic) granulomatosis with polyangiitis (n=11) and IPF (n=68). Patients with Scadding stage 4 had the highest serum SAA levels and these were significantly increased compared to those without fibrosis.…”
Section: Serum Amyloid Antigen (Saa)mentioning
confidence: 99%